On Quivers and Incidence Algebras (Global Journal of Science Frontier Research, 2012)
By giving a generalized definition for the quiver algebra we obtain a surjective homomorphism between the quiver algebra of locally finite acyclic quiver and the incidence algebra of corresponding poset.
Keywords: Incidence algebra; Quiver; Path algebra